PENGARUH SELF REGULATED LEARNING (SLR) TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Amanda Utari; Syamsul Hadi Senen; Rasto Rasto (Sosio-Didaktika: Social Science Education Journal, 2018)
In the world of education, learning achievement is very important and become one of the benchmarks of learning achievement. Success in teaching and learning can be achieved from the results of learning achieved by learners. Learning achievement by two factors, in internal factors and external factors. Internal factors of this student, such as physiological and psychological factors. While the external factors of this student are students, such as family environment, school and community environment. The learning theory of Albert Bandura known as the Social Learning Theory (social learning theory) with the concept of the accuracy of reciprocal determinations, suggests a constant interaction between environments, behaviors and people who are learning the process that will ultimately affect the achievements that result. The theory of social learning from Albert Bandura which is a process of learning external and internal factors.